Burnout amongst clinical and counselling psychologist: The role of early maladaptive schemas and coping modes as vulnerability factors. (2nd October 2018) - Simpson, Susan; Simionato, Gabriella; Smout, Matthew; van Vreeswijk, Michiel F.; Hayes, Chris; Sougleris, Christina; Reid, Corinne
Abstract: Psychologists are subject to multiple competing emotional demands that increase the risk of burnout. Research has demonstrated that burnout arises from both organizational and personal factors, including psychologists' personal beliefs and coping. Preliminary research indicates that early maladaptive schemas (EMS) are associated with high burnout, yet, to date, the role of EMS and associated coping responses (maladaptive coping modes [MCM]) in predicting high burnout amongst psychologists has not been investigated. Four hundred forty‐three psychologists completed a self‐report online questionnaire comprising the Maslach Burnout Inventory—emotional exhaustion scale (EE), Young Schema Questionnaire, and Schema Mode Inventory. The two most common EMS amongst psychologists were unrelenting standards and self‐sacrifice. There was substantial indication of burnout, with 18.3% in the high range and 29.6% in the moderate range of EE. The most common MCM were detached protector and detached self‐soother. Controlling for demographics and job demands, EMS accounted for an additional 18% variance in EE. MCM accounted for an additional 6% beyond the variance explained by demographics, job demands, and EMS. Practical recommendations are suggested to reduce psychologist burnout.